The Study Effectiveness of Implementation of Development Strategic Plan for Phetchabun Province - Weerasin, Witoon (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of the research article were 1) to study Phetchabun's development strategic plan, 2) to study the process of bring Phetchabun, development strategic plan into action, 3) to study effectiveness the of Phetchabun development strategic plan in to action. This research uses qualitative research bring methodology. The data was collected from in-depth interviews by purposive selection from 25 experts on strategic planning, professionals, provincial administrators and stakeholders. The tool for collecting data was structured interview. The research results were found that: 1. General condition of the Phetchabun province prepared provincial development strategic plan in accordance with government policy and potentials of province. 2. The process of implementing the provincial development strategic plan consisted of 4 steps: 1) the study of the strategic plan 2) implementation of the strategic development plan 3) monitoring and evaluation 4) Performance summary 3. As for Effectiveness of the implementation of Phetchabun’s development strategic plan, was found that: Satisfaction of employees, the results were found that : 1) the superiors paid attention, organizations needed personnel to work with accuracy, 2) the superiors encouraged all timeม 3) there was integration in the organizations, 4) there was support and assistance from executives and superiors, 5) on control, organizations had rules, regulations and direct supervision 6) there was a reward system, 7) there was management of conflict. On satisfaction of people, the results were found that: 1) The people understood and were eager to know what they got from strategic plan 2) Some issues and projects were not targeted because the mobilization of people was not diversified, direction was from the central 3) The government participated in making the grassroots population more profitable and more satisfactory.